Dual role of lactate in human health and disease - Kumar, Sudhir; Sahu, Neha; Jawaid, Talha; Jayasingh Chellammal, Hanish Singh; Upadhyay, Prabhat (Frontiers in Physiology, 2025)
Lactate, traditionally seen as a byproduct of anaerobic metabolism, has gained attention for its dual role in human health. While it is associated with muscle fatigue, lactate also plays a crucial role in various physiological and pathological processes. This review explores lactate’s dual nature as both beneficial and detrimental. Under normal physiological conditions, lactate is an essential energy substrate, involved in the Cori cycle, where it is converted back to glucose in the liver. However, excessive lactate accumulation is linked to health issues, including cancer, metabolic disorders, and neurological diseases. The Warburg effect in cancer, characterized by increased lactate production even in oxygen-rich environments, promotes tumor progression and therapy resistance. In diseases like malaria and ischemic stroke, high lactate levels contribute to tissue damage and metabolic disturbances. Recent research also highlights lactate’s beneficial roles, including regulation of immune responses, enhanced exercise performance, and neuronal signaling. Furthermore, gut microbiota significantly impacts lactate metabolism, where beneficial bacteria use lactate to maintain gut health, while some pathogenic bacteria exacerbate disease through excess lactate production. Emerging therapeutic potential of lactate, including lactate dehydrogenase inhibitors, offers promising treatment avenues. This review provides a comprehensive overview of lactate’s complex role in health and disease, emphasizing the need for targeted strategies to harness its benefits while mitigating its harmful effects.